Initial cognitive changes in Parkinson’s disease - Weintraub, Daniel (Mov Disord, 2018)
The focus on cognitive impairment in neurodegenerative diseases, including Parkinson’s disease (PD), is shifting from the dementia stage to earlier stages of impairment, including mild cognitive impairment (MCI). This shift is driven primarily by the desire to improve long-term outcomes by delivering therapeutic interventions earlier in the clinical course, even pre-symptomatically in those at highest risk, and at the initial stage in the pathophysiological cascade that underpins common dementia syndromes. This manuscript focuses on key findings and challenges in studying earliest stages of cognitive decline in PD, including a detailed examination of neuropsychological testing, cognitive performance in early and prodromal PD, epidemiological research for PD-MCI to date, and expert recommendations for assessment.